Geometric effect analysis of highway-rail grade crossing safety performance. (April 2020) - Keramati, Amin; Lu, Pan; Tolliver, Denver; Wang, Xingju
Highlights: Survival analysis in highway rail grade crossing safety analysis is introduced. Crossing geometric factors, traffic exposure, and highway/railway characteristics are found significant contributors. Effects on crash frequency and crash severity are researched. Geometric factors' long-term effects on cumulative probability of crash severity and occurrence over 30 years is evaluated. Crossings with three main tracks contribute the highest long-term crash probability. Abstract: Highway-rail grade crossings (HRGCs) are where a roadway and railway intersect at the same level. Safety at HRGCs has been identified as a high-priority concern among transportation agencies, but there has been little research on the effects of HRGC geometric parameters on their safety performance. This paper evaluates the effects of HRGC geometric parameters on crash occurrence and severity likelihoods. The competing risk algorithm is selected to simultaneously analyze crash occurrence and severities. Four main HRGC geometric factors, along with other contributors, are investigated at 3, 194 public HRGCs in North Dakota. This study focuses primarily on four geometric features of an HRGC: (1) acute crossing angle, (2) number of tracks (indicator of crossing width), (3) the roadway distance between the HRGC and the signalized intersection, and (4) number of highway lanes. Distance to the nearest roadway intersections and highway-railway crossing angles are map-based calculations drawn from geographic information systems (GIS). The findings are: (1) all contributors tested in this study, including highway characteristics, traffic exposures from both railway and highway, and the four geometric features, significantly affect at least one crash severity level; (2) all contributors significantly impact crash frequency except for the distance between crossings and the nearest roadway intersection; and (3) geometric parameters' long-term effects on cumulative probability of crash severity and occurrence over 30 years is also evaluated. Crossings with three main tracks contribute the highest long-term crash probabilities.